Hubungan Persepsi Dukungan Sosial dengan Perilaku Personal Hygiene Saat Menstruasi pada Remaja Awal di SMPI Al-Munir Bekasi - Yuliawati, Diani; Mulyanto, Tatag (MAHESA : Malahayati Health Student Journal, 2025)
ABSTRACT Personal hygiene behavior during menstruation is an action in maintaining health and hygiene in the female area during menstruation. Poor personal hygiene behavior during menstruation can cause disruption in the function of the reproductive organs. Personal hygiene behavior is influenced by the perception of social support that lacks knowledge. This study aims to determine the relationship between the perception of social support and personal hygiene behavior during menstruation in early adolescents. The type of research is quantitative with the design of this study being cross sectional. The number of respondents in this study is 48 young women. This research is quantitative analysis and sampling technique, namely chi square. The sampling method in this study  is Non Probability sampling with a total sampling approach. The data presentation is carried out using a frequency distribution table. The results of the study showed that the perception of social support was relatively low (72.9%) and poor personal hygiene behavior (60.4%). From the bivariate analysis, there was a relationship between the perception of social support and personal hygiene behavior during menstruation in early adolescents at SMPI Al-Munir (p=0.001). This study suggests that adolescents should be more active in seeking more in-depth information on how to take good and correct care of the female organs during menstruation, improve personal hygiene behaviors during menstruation with knowledge and experience obtained from family, friends or the media. For the school, you can collaborate with the nearest agency or health worker to hold a seminar on menstrual hygiene management and can advise or train students at school about personal hygiene behavior so that students behave positively towards themselves during menstruation. Keywords: Menstruation, Personal Hygiene Behavior, Perception of Social Support, Young Women  ABSTRAK Perilaku Personal hygiene saat menstruasi merupakan suatu tindakan dalam memelihara kesehatan serta kebersihan pada daerah kewanitaan pada saat menstruasi. Perilaku personal hygiene yang tidak baik saat menstruasi bisa menyebabkan terganggunya fungsi organ reproduksi. Perilaku personal hygiene dipengaruhi oleh persepsi dukungan sosial yang kurang dalam pengetahuan. Penelitian ini bertujuan untuk mengetahui hubungan persepsi dukungan sosial dengan perilaku personal hygiene saat menstruasi pada remaja awal. Penelitian ini menggunakan jenis penelitian kuantitatif dengan desain penelitian ini adalah cross sectional. Jumlah responden dalam penelitian ini 48 remaja putri. Penelitian ini bersifat analitik kuantitatif dan teknik pengambilan sampel yaitu chi square. Metode pengambilan sampel dalam penelitian ini Non Probability sampling dengan pendekatan total sampling. Penyajian data dilakukan dengan menggunakan tabel distribusi frekuensi. Hasil penelitian ini menunjukkan persepsi dukungan sosial tergolong rendah sebesar (72,9%) dan perilaku personal hygiene buruk (60,4%). Dari analisa bivariat ada hubungan persepsi dukungan sosial dengan perilaku personal hygiene saat menstruasi pada remaja awal di SMPI Al-Munir (p=0,001). Peneliti menyarankan untuk para remaja agar lebih aktif mencari informasi lebih mendalam bagaimana cara merawat organ kewanitaan yang baik dan benar saat menstruasi meningkatkan perilaku personal hygiene saat menstruasi dengan pengetahuan dan pengalaman yang diperoleh dari keluarga, teman atau media masa. Peneliti juga menyarankan bagi pihak sekolah dapat bekerjasama dengan instansi atau tenaga kesehatan terdekat untuk mengadakan seminar tentang manajemen kebersihan menstruasi dan dapat menasihati atau melatih pengetahuan siswi di sekolah tentang perilaku kebersihan diri agar siswi berperilaku positif terhadap dirinya saat menstruasi. Kata Kunci: Menstruasi, Perilaku Personal Hygiene, Persepsi Dukungan Sosial, Remaja Putri